Condições e organização do trabalho no SUS em dois hospitais públicos sob diferentes formas de gestão na perspectiva de médicos e enfermeiros - Costa, Sheila Araujo [UNIFESP] (2017)
This study aims to capture and analyze, from the perspective of physicians and nurses, the working organization and conditions in two hospitals under different management forms -- direct administration- Adm and social organization – OS- both components of the public health system of a large municipality of greater São Paulo. As a major methodological step, the Questionnaire on Working Conditions (qCT) was validated in its quantitative dimension as an instrument for evaluating the working organization and conditions. In a second moment, in a quantitative study, the qCT was applied, objectifying to identify and discuss the working organization and conditions of nurses and physicians in two hospitals under different management forms. The sample of the first phase consisted of 689 health professionals working in the public health system under the Health Secretary management. The analysis of the main components has shown the existence of six factors, grouped by pairs in three sets, all of which have shown high internal consistence, with Cronbach's alpha of 0.96 and Confirmatory Factor Analysis ≥ 90 (values above 90 being accepted). The data indicates that the Working Conditions Questionnaire reliably reproduces the structure of the assumed theoretical model and combines the necessary technical properties that allow working conditions in health services to be properly reviewed. In the second phase, 181 questionnaires were answered, distributed as follows: 88 in the Adm hospital and 93 in the OS hospital. At the Adm hospital, 54 were doctors and 39 were nurses. At the OS hospital 57 were doctors and 31 were nurses. The categorical data were presented by frequencies and proportions, while the numerical data were described by means and standard deviations. Analyzing the answers obtained, a tendency is drawn, notably among physicians, of acceptance of private employment bonds, and even valuation of the private sector. Among the nurses, it is noted the ambiguity in relation to working conditions and answers marked by acquiescent attitudes towards the rules of the organization. These positionings are analyzed through a theoretical referential which places hospital assistance under OS management as an enterprise turned advantageous in a context of appropriation of public funds by failing medical businesses, with an imposition of instability of employment bonds and colonization of the public sphere by neoliberal values, such as entrepreneurship, massively propragandized by mass media and accepted by the middle classes, to which most of the physicians and nurses which took part in this research belong to.